Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Disiplin Kerja Pegawai Badan Pengembangan Sumber Daya Manusia Industri - Solihat, Sarah Annisa; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the effect of work environment (X1) and work motivation (X2) on employee work discipline (Y) in the General Division of the Industrial Human Resource Development Agency. The research used a quantitative approach with a survey method involving 42 respondents. Data were processed using SPSS version 26. The results of the partial test (t-test) show that the work environment (X1) has a positive and significant effect on work discipline, with a t-value of 2.449 greater than the t-table value of 2.023, and a significance level of 0.019 < 0.05. Meanwhile, work motivation (X2) does not have a significant effect on work discipline, as indicated by a t-value of -0.432 which is less than the t-table value of 2.023, and a significance level of 0.668 > 0.05. Simultaneously, the F-test results show that the work environment and work motivation together have a significant effect on work discipline, with an F-value of 3.348 greater than the F-table value of 3.24, and a significance level of 0.001 < 0.05. This study concludes that improvement in employee work discipline is more influenced by a conducive work environment than by work motivation. Keywords: work environment, work motivation, employee work discipline